La investigación y la enseñanza de la historia reciente en Uruguay - Bertinat, Juanita; Rubio, Adriana (2016)
Dos formadoras de docentes reflexionan sobre la relación entre enseñanza e investigación de la historia reciente en Uruguay. A partir de su biografía personal aportan pistas para la comprensión de los contextos políticos, sociales y educativos de las últimas décadas en su país.
Two teacher's trainers reflect on the relationship between teaching and research in recent history in Uruguay. From their personal biography they provide clues to the understanding of the political, social and educational contexts of the last decades in their country
Keywords: Historia investigada; Historia enseñada; Historia reciente; Uruguay; History investigated; History taught; Recent history; Uruguay